2006
DOI: 10.1097/01.qai.0000188122.15493.0a
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in HIV-Infected and Uninfected Children of HIV-Infected and Uninfected Mothers in Rural Uganda

Abstract: More than half of HIV-infected infants died at less than 2 years of age. Therefore, ART may need to be initiated earlier in HIV-infected African children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
155
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(165 citation statements)
references
References 11 publications
7
155
3
Order By: Relevance
“…Cohort studies from other sub-Saharan countries have shown that, before the availability of ART, HEU children had a higher mortality risk than HIV-unexposed children [4,6,29]. However, reports on mortality in HEU and HIVunexposed children in the ARTera are scarce, and results are heterogeneous [19,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Cohort studies from other sub-Saharan countries have shown that, before the availability of ART, HEU children had a higher mortality risk than HIV-unexposed children [4,6,29]. However, reports on mortality in HEU and HIVunexposed children in the ARTera are scarce, and results are heterogeneous [19,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 83%
“…Direct or indirect HIV exposure in utero, intra partum or during breastfeeding may confer risks even in the absence of infection. Several studies have described increased mortality and enhanced risk of poor health and growth outcomes in HEU compared with HIV-unexposed children [4][5][6][7][8][9][10][11]. However, the nature of the vulnerability of the HEU children is not entirely clear.…”
Section: Introductionmentioning
confidence: 97%
“…It others setting very high mortality rate where found in infants who were not on ARV compared to those receiving ARV treatment (14). Death occurred in our study at a median age of 7 months; HIV infection increased the death rate before the age of 2 years considerably (39,40). The survival rate was low (43.3%) in children who were not treated, against 84.3% in those on ARV treatment.…”
Section: Discussionmentioning
confidence: 55%
“…1 The progression of HIV infection in children is very aggressive and many children die during their young age. 2 In India the estimated number of children under 15 years is 4%. A collaborative study on the growth patterns of HIV infected (184) and uninfected (1403) children.…”
Section: Introductionmentioning
confidence: 99%